2018
DOI: 10.22502/jlmc.v6i1.210
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception of Public Towards Medico Legal Autopsy in Nepal

Abstract: Introduction: Autopsy is an important tool to determine the cause of death. This study was conducted with the objectives to assess the knowledge and perception of Nepalese people towards medico legal autopsy. Methods: It was a questionnaire based cross sectional study performed among the general public of Nepal. A standard pretested questionnaire was used to collect the responses on knowledge and perception of the people about medico legal autopsy. Independent samples t-test was used to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Despite the fact that the population included in our sample is not completely representative of Vietnam, the results showed several commonalities found in previous studies on similar topics. Recent research from Nepal and Pakistan with the general public showed similar findings to our study about the benefit of CDA in identifying CoD, especially in cases of (forensically) suspicious death [18,19]. They also found similar reasons for objecting autopsy.…”
Section: Plos Global Public Healthsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite the fact that the population included in our sample is not completely representative of Vietnam, the results showed several commonalities found in previous studies on similar topics. Recent research from Nepal and Pakistan with the general public showed similar findings to our study about the benefit of CDA in identifying CoD, especially in cases of (forensically) suspicious death [18,19]. They also found similar reasons for objecting autopsy.…”
Section: Plos Global Public Healthsupporting
confidence: 89%
“…Particularly, in this study, body disfigurement from autopsy served as one of the main reasons for disapproving the method. This was also frequently found in the context of studies conducted in other LMICs, such as Nepal and Pakistan with participants from the general public [18,19]. While participants from our study largely identified as non-religious (i.e.…”
Section: Plos Global Public Healthsupporting
confidence: 79%
See 1 more Smart Citation
“…It's been estimated that one-third of death certificates are inaccurate and around 50% of autopsies uncovered previously unknown medical issues. 22 Autopsy therefore serves an important purpose to identify unknown inheritable genetic diseases and outbreaks allowing healthcare system to take pre-emptive measures. This may further serve to assess efficacy of commonly used diagnostic and therapeutic capabilities, allowing detection of diagnostic errors, malpractice and further potential for improvements.…”
Section: Knowledge Perceptionmentioning
confidence: 99%
“…Therefore, households use other water sources for drinking purposes, such as jarred water, groundwater, and tanker water [26,27]. However, it was reported that these water sources are also contaminated with total coliforms (TC), exceeding Nepal's National Drinking Water Quality Standards (NDWQS) [28][29][30][31]. The Nepal Burden of Disease Report in 2017 identified unsafe drinking water as one of the high-risk factors for mortality across all ages and genders [32].…”
Section: Introductionmentioning
confidence: 99%